Growth and Pubertal Development Among HIV Infected and Uninfected Adolescent Girls in Lagos, Nigeria: A Comparative Cross-Sectional Study - David Agatha; Gbaja-biamila Titilola; Salako Abideen; Odubela Oluwatosin; Wapmuk Agatha; Ekama Sabdat; Musari-Martins Tomilola; Ezemelue Priscilla; Herbertson Ebiere; Ezechi Oliver (SAGE Publishing, 2022)
This study aimed to compare growth and pubertal developmental parameters among HIV-infected and uninfected adolescent girls (11-19 years) in Lagos using a cross-sectional approach. Height, weight, BMI Z -scores, sexual maturity rating by Tanner stages and age at menarche, were compared in the 2 groups. The mean age was similar in both groups (13.2 [±2.3] years and 13.6 [±1.6] years for HIV positive and negative respectively [ P = .13]). Majority (66.2%) were in Junior Secondary classes and the mean socioeconomic class was 2.5 (±0.9). HIV-infected girls had significantly lower height, weight, and BMI Z scores compared to their uninfected counterparts. The proportion that had attained Tanner stages 3 to 5 were significantly lower among the HIV-positive participants. The study identified lower growth parameters and pubertal delay among HIV-infected adolescent females compared to HIV uninfected girls. Growth and sexual maturation assessment should form part of routine care of adolescents living with HIV.